Household Food Waste Research: The Current State of the Art and a Guided Tour for Further Development - Oláh, Judit; Kasza, Gyula; Szabó-Bódi, Barbara; Szakos, Dávid; Popp, József; Lakner, Zoltán (Frontiers in Environmental Science, 2022)
Decreasing food waste is an important contribution to the practical achievement of Sustainable Development Goals of the United Nations. The last decades witnessed a dynamic expansion of food waste-related publications, parallel with this studies, systematic reviews and bibliometric analyses had been published on this topic. The novelty of the current publication is threefold: (1) it summarises recent publications, and puts their results into development context; (2) applies the triangulation method by analysing the food waste-based literature from the aspect of epistemological development, structural composition and scientometric mapping, (3) based on in-depth research of the literature and the determination of the most important ways of its development, the key steps of a modern waste research project as a function of research goals as well as available financial resources are outlined. The bibliometric research based on nearly three thousand resources has shown a considerable geographic disparity in food waste research: these topics are investigated mainly in developed and emerging countries. Bibliometric mapping highlights the importance of the application of qualitative methods for exploring motivational drivers and actual behaviour of households. A general workflow for food waste research is suggested by the authors based on a study carried out in developed countries. This method can be considered as a general, flexible framework, which could serve as a common platform for experts. The framework can be used independently from the of economic development level of the countries but it is especially useful for researchers in the global South because experiences gained by developed countries opens a favourable possibility to conceptualise, plan, realise and publish their food-waste related research.